A Note on Self-heating and Spontaneous Combustion of Stored Sunflower Seed Cake and Cotton Seeds (University of Khartoum Journal of Agricultural Sciences, 2023)
Sunflower seed cake and cotton seed warehouses combusted spontaneouslyand burnt in August and November 2009, respectively, in Khartoum North industrialarea. The objective of this study was to determine some of the reasons for self-heatingand spontaneous combustion. Representative samples from the two warehouses werecollected. Aspergillus niger, A. flavus, Paesiolomyces sp., Rhizopus oryzae, Absidia sp.were isolated at 37 o C. Bacillus thuringiensis was isolated at 37 oC, and B. pantothenticus,B. ciculans, B. licheniformis, B. sphaericus, B. badius, Escherichia coli and Klebsiellasp. were isolated at 60 oC. A decrease in oil, fibre and phosphorus and increase in freefatty acids and protein contents were detected.
Keywords: Self-heating; combustion; sunflower seed cake; cotton seeds